The complete mitochondrial genome of Mazocraeoides gonialosae (Platyhelminthes: Monogenea) from dotted gizzard shad, Konosirus punctatus - Jeong-Ho Kim; U-Hwa Nam; Hana Kim; Ilson Whang (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitogenome of Mazocraeoides gonialosae parasitized on the gills of dotted gizzard shad (Konosirus punctatus) was obtained. The entire circular mitogenome size of M. gonialosae was 15,106 bp, containing 12 protein-coding genes (PCGs; lacking atp8 gene), 2 rRNA genes, 22 tRNA genes, 1 repeat region, and several non-coding regions. The arrangement of the 12 PCGs was identical with those of other polyophistocotylean monogenean mitogenomes available in GenBank. The phylogenetic tree based on the concatenated 12 PCGs revealed that M. gonialosae belonged to the mazocraeid clade, together with Neomazocraes dorosomatis.